Sistema y tecnología de transporte en un modelo intra-metropolitano estático de localización residencial - Vivas Pacheco, Harvy (Sociedad y Economía, 2008)
According to the classical theories of the central place, this article proposes a static metropolitan model of residential localization wich includes explicitly a function of total cost of travel. This proposal conjugates the main contributions of Wingo (1961) with the micro-foundations of the modern urban economy theory.